Development of Fast Reliable Secure File Transfer Protocol (FRS-FTP) (مجلة المنصور, 2022)
There is a great need to transfer information between hosts and networks in fast with reliable and secure way; this is a big challengewith open environment especially Internet and TCP based Networks.There are several extra file transfer protocols behind core FTP protocol, but each of them suffer from either slow, unreliable orunsecure workflow.In this paper, we develop a new file transfer protocol based on UDP as a fast, reliable and secure protocol; and called FRS-FTP (refers toFast Reliable Secure File Transfer Protocol. The proposed protocol based on three phases, the first phase to enforce the "reliability"issue using cryptographic hash checksum, the second phase to enforce the "security" issue using file encryption/decryption, portprotection and authentication, while the third phase to transfer files with "fast" issue under UDP.The proposed protocol is implemented using Visual Basic .Net programming language and System.Net.Sockets embedded dot NetClass.